The Meaning of Psychological Calm for Gold Investors in the Midst of Global Uncertainty: A Phenomenological Study of Safe Haven Assets - Asikin, Muhamad Zaenal; Sulistiawati, Lina (Politeknik Siber Cerdika Internasional, 2026)
This research aims to understand the meaning of psychological calm felt by gold investors in the midst of global uncertainty through a phenomenological approach. World economic instability triggered by global inflation, geopolitical conflicts, and international trade tariff policies are increasing financial anxiety and market volatility. In such situations, gold is known as a safe haven asset, but most previous research has focused on quantitative aspects such as price correlation and volatility. This study uses a phenomenological qualitative approach with in-depth interview techniques with 10 experienced gold investors and an exploratory questionnaire with 35 novice investors. The analysis was carried out using Interpretative Phenomenological Analysis (IPA). The results of the study show that gold is interpreted as a symbol of stability, a reduction of financial anxiety, and a means of building a sense of control over the future. Gold ownership provides psychological peace that is not only based on price stability, but also on historical beliefs and the symbolic value of security. Case studies show that consistency in saving gold can be an effective strategy in achieving long-term goals without financial pressure. This study concludes that gold functions as a psychological safe haven that integrates economic stability and emotional regulation in the face of global uncertainty.